Quantifying Eruptive and Background Seismicity, Deformation, Degassing, and Thermal Emissions at Volcanoes in the United States During 1978–2020. Issue 6 (1st June 2021) - Reath, K.; Pritchard, M. E.; Roman, D. C.; Lopez, T.; Carn, S.; Fischer, T. P.; Lu, Z.; Poland, M. P.; Vaughan, R. G.; Wessels, R.; Wike, L. L.; Tran, H. K.
Abstract: An important aspect of volcanic hazard assessment is determination of the level and character of background activity at a volcano so that deviations from background (called unrest) can be identified. Here, we compile the instrumentally recorded eruptive and noneruptive activity for 161 US volcanoes between 1978 and 2020. We combine monitoring data from four techniques: seismicity, ground deformation, degassing, and thermal emissions. To previous work, we add the first comprehensive survey of US volcanoes using medium‐spatial resolution satellite thermal observations, newly available field surveys of degassing, and new compilations of seismic and deformation data. We report previously undocumented thermal activity at 30 volcanoes using data from the spaceborne ASTER sensor during 2000–2020. To facilitate comparison of activity levels for all US volcanoes, we assign a numerical classification of the Activity Intensity Level for each monitoring technique, with the highest ranking corresponding to an eruption. There are 96 US volcanoes (59%) with at least one type of detected activity, but this represents a lower bound: For example, there are 12 volcanoes where degassing has been observed but has not yet been quantified. We identify dozens of volcanoes where volcanic activity is only measured by satellite (45% of all thermal observations), and other volcanoes where only ground‐based sensors have detected activity (e.g., all seismic and 62% of measured degassing observations). Our compilation provides a baseline against which future measurements can be compared, demonstrates the need for both ground‐based and remote observations, and serves as a guide for prioritizing future monitoring efforts. Plain Language Summary: We have compiled the instrumentally recorded eruptive and noneruptive activity in terms of earthquakes, ground deformation, degassing, and thermal emissions for 161 US volcanoes between 1978 and 2020. There are 96 US volcanoes (59%) with at least one type of detected activity. But we think that more than 96 volcanoes had activity during this time period because of the limits in the data available. We report previously undocumented thermal activity at 30 volcanoes using data from the spaceborne ASTER sensor measured in the Thermal Infrared during 2000–2020. We identify dozens of volcanoes where volcanic activity is only measured by satellite (45% of all thermal observations), and other volcanoes where only ground‐based sensors have detected activity (e.g., all seismic and 62% of measured degassing observations). Our compilation provides a baseline against which future measurements can be compared, demonstrates the need for both ground‐based and remote observations, and serves as a guide for prioritizing future monitoring efforts. Key Points: In the United States, 96 of 161 volcanoes have at least one type of detected activity (seismicity, deformation, and gas or thermal emissions) Forty‐five percent of volcanoes with thermal emissions are only seen by medium‐spatial resolution satellites (<100 m/pixel) Each volcano has an Activity Intensity Level; a higher score from multiple data types indicates a greater likelihood of magmatic activity